2013
DOI: 10.1002/qj.2179
|View full text |Cite
|
Sign up to set email alerts
|

A posteriori diagnostics of the impact of observations on the AROME‐France convective‐scale data assimilation system

Abstract: AROME-France is an operational convective-scale numerical weather prediction system which uses a 3D-Var assimilation scheme in order to determine its initial conditions. In addition to conventional and satellite observations, regional high-resolution observations are assimilated, such as screen-level observations, total zenith delays from ground-based GPS stations and radar measurements (radial winds and reflectivities). The impact of the various observation types on AROME-France analyses is assessed using an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…7 for the experiment OREFLEC. The RH field of the 3D-Var analysis is clearly constrained by the RH retrievals since nearly all points verify the following ranking: y These results are consistent with the recent computations of a posteriori diagnostics of the impact of observations on the analysis of the AROME 3D-Var assimilation system (Brousseau et al 2013). They computed the reduction of the estimation error variance and showed the large impact of the radar observations on the analyzed model fields, in particular that the relative humidity pseudo-observations retrieved from the radar reflectivities contribute the most to the variance reduction of specific humidity in the midatmosphere during precipitating periods.…”
Section: ) General Behaviorsupporting
confidence: 85%
“…7 for the experiment OREFLEC. The RH field of the 3D-Var analysis is clearly constrained by the RH retrievals since nearly all points verify the following ranking: y These results are consistent with the recent computations of a posteriori diagnostics of the impact of observations on the analysis of the AROME 3D-Var assimilation system (Brousseau et al 2013). They computed the reduction of the estimation error variance and showed the large impact of the radar observations on the analyzed model fields, in particular that the relative humidity pseudo-observations retrieved from the radar reflectivities contribute the most to the variance reduction of specific humidity in the midatmosphere during precipitating periods.…”
Section: ) General Behaviorsupporting
confidence: 85%
“…The influence matrix is defined as the derivative (Jacobi matrix) of the analysis vector in observation space with respect to the vector of observations. A study by Brousseau et al (2013) using this method has shown consistency with results from error variance reduction (Desroziers et al, 2005). The limitation of these methods is that they only describe the analysis influence of observations, which is an interesting quantity itself and likely related to the forecast impact of observations.…”
Section: Introductionmentioning
confidence: 74%
“…The background error covariance matrices were specified through the use of an ensemble method (Brousseau et al, 2011). Data assimilated by the AROMEFrance DA system included observations from radiosondes, wind profilers, aircrafts, ships, buoys, automatic weather stations, satellites, GPS stations, and both Doppler radar wind velocity and radar reflectivity (Brousseau et al, 2014).…”
Section: Locationmentioning
confidence: 99%